A Method of Team Cognitive Process Modelling of Air Traffic Controller in En route ATC - FURUTA, Kazuo; INOUE, Satoru; KANNO, Taro; AOYAMA, Hisae (Electronic Navigation Research Institute papers, 2024)
In recent years, various efforts have been made in Air Traffic Control (ATC) to maintain traffic air safety and efficiency in the face of increasing air traffic demands. ATC is a complex process that depends to a large degree on human capabilities. Understanding how controllers carry out their tasks is an important factor for the design and development of ATC systems. In particular, the human factors are considered to be a serious problem for air traffic safety control, in both major and minor incidents. Therefore, the need to analyze mechanisms by which errors occur due to complex factors and to develop systems that can deal with these errors is increasing. From the cognitive process perspective, it is essential that systems developers have an understanding of the more complex working processes that involve cooperative work of multiple controllers. Distributed cognition is one of the methodological frameworks to analyze cognitive processes that spans multiple actors mediated by technology. In this research, we attempt to analyze and model interactions that take place in en route ATC systems based on distributed cognition. We conducted ethnographic field observation at the Tokyo Area Control Centre and then analyzed the data to develop a cognitive model of team cooperation. The analysis revealed that the mutual belief model is applicable to team cooperation processes, the role assignment of tasks within a controller team is implicit, and that control plans are implemented smoothly once team situation awareness has been established. A cognitive model of controllers’ team cooperation has been constructed based on these findings. We examined the functional problems in an ATC system from the human factors aspect, and concluded that solution of this problem needs some kinds of measures. This research focuses on developing analysis method for modelling of the air traffic controller’s cognitive process.